Simultaneous Spectrophotometric Estimation of Esomeprazole and Domperidone in Solid Dosage Forms (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
This study aimed to develop a simple, accurate, precise, sensitive, and cost-effective UV spectrophotometric method for the simultaneous estimation of Esomeprazole (ES) and Domperidone (DP) in tablet dosage forms. Two analytical methods were employed: the simultaneous equation method (Method I) and the absorbance ratio method (Method II). In Method I, wavelengths of 300 nm and 284 nm were selected for the estimation of ES and DP, respectively. In Method II, 294 nm was selected as the iso-absorptive point, while 284 nm corresponded to the maximum absorbance of DP. Both drugs obeyed Beer–Lambert’s law within the concentration range of 2–10 μg/mL. The percentage assay values for both drugs were found to be close to 100%, indicating excellent accuracy, and recovery studies confirmed almost complete recovery. The proposed methods were validated according to ICH guidelines for accuracy, precision, and specificity. The results demonstrated that both methods are reliable, reproducible, and suitable for routine quality control analysis of Esomeprazole and Domperidone in combined tablet dosage forms.
Keywords: Domperidone; Esomeprazole; effective UV spectrophotometric method; ICH guidelines